Is It Possible to Produce Meat Without Animals? The Potential of Microorganisms as Protein Sources - Alan Portal D’Almeida; Tiago Lima de Albuquerque (Fermentation)
Climate change and environmental impacts from greenhouse gas emissions have spurred on efforts to reduce these emissions. Meat production, especially from cattle, is a significant contributor, releasing methane—a greenhouse gas far more potent than CO2—and driving deforestation for pastureland. As a sustainable alternative, Single-Cell Protein (SCP), derived from microorganisms like bacteria, yeast, and algae, offers high nutritional value with a lower environmental impact. SCP production has advanced through process optimization, the use of eco-friendly substrates such as agro-industrial and food waste, and the cultivation of safe microorganisms classified as Generally Regarded as Safe (GRAS). Innovations in flavor and texture, including the use of myoglobin and natural polymers to mimic meat properties, have further improved SCP’s appeal. Despite these advances, challenges remain in optimizing production parameters, enhancing sensory acceptance, and ensuring regulatory compliance for market introduction. This review explores the potential of SCP to serve as a sustainable protein source, addressing both environmental concerns and nutritional demands. It highlights recent advancements in production techniques and sensory improvements while discussing their role in environmentally friendly and health-conscious food systems. SCP stands out as a promising solution for reducing greenhouse gas emissions, offering an efficient and sustainable alternative to conventional protein sources.